Probabilistic Progressive Collapse Analysis of 3D Steel Moment Frame Using Fragility Curves - E. Mohammadi Dehcheshmeh; V. Broujerdian; Gh.R. Ghodrati Amiri (مهندسی عمران شریف, 2022)
Previous studies indicate that low-rise buildings are more prone to progressive collapse rather than high-rise ones. In this research, an innovative method of probabilistic analysis of progressive collapse has been applied based on the concept of fragility curves. In order to develop the fragility curves, the column reaction is considered as the Intensity Measure (IM) and the displacement at top of the removed column as the Damage Index (DI). Based on these measures, the fragility curves of a 4-story steel Intermediate Moment Frame (IMF) structure were developed. Six scenarios of progressive collapse including removal of corner, perimeter, and middle columns were investigated. The scenarios were considered in all columns of structural stories. The simulations were conducted in OpenSees software. The structural analyses were performed by the nonlinear time history approach in a three-dimensional framework. The verification of the numerical modeling process was performed using the available experimental data. The results showed that the IDA capacity curve of the upper stories was weaker than the lower stories. According to the results, at every considered DI and assumed performance level, damage to the removed columns occurs at lower axial force on the upper stories than on the lower ones. Furthermore, the potential of the progressive collapse in different columns was investigated. It was shown that the capacity curve of the middle columns was lower than other columns due to the high gravity loads. The probabilities of the fragility of the corner and the perimeter column in the stories were the highest and the lowest, respectively. In order to reach the corner and the perimeter column to CP performance level, 93% axial force and 105% of the axial gravity load in the opposite direction of the column reaction were required. Finally, the overall fragility curves of the structure were investigated. According to the results, upon removing 100% of the column reaction in each column of the considered 4-story structure, the structure exceeded the CP performance level.